2018
DOI: 10.1007/s00240-018-1047-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of perirenal fat volume in patients with nephrolithiasis

Abstract: The concept of adipose tissue as an organ unto itself represents a new medical construct; already differences in the volume of perirenal fat around a tumor-bearing kidney have been described. We hypothesized that renal calculi may have similar impact on perirenal fat or alternatively abnormalities in urinary metabolites may be the result of perirenal fat affecting renal metabolism and subsequent stone formation. Accordingly, we conducted a study utilizing three-dimensional imaging software to evaluate perirena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Recently, a study by Lama et al. [ 10 ], in 40 patients with unilateral nephrolithiasis undergoing percutaneous nephrolithotomy as the primary treatment, showed that the mean PFV of stone-bearing kidneys was significantly greater than non-stone-bearing kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study by Lama et al. [ 10 ], in 40 patients with unilateral nephrolithiasis undergoing percutaneous nephrolithotomy as the primary treatment, showed that the mean PFV of stone-bearing kidneys was significantly greater than non-stone-bearing kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study of Lama et al. with a small patient cohort ( n = 40) showed that stone-bearing kidney has a greater perirenal fat volume (PFV) than non-stone-bearing kidney [ 10 ]. However, the calculation of PFV on computerized tomography (CT) scans requires the use of specific imaging software, which may be unavailable in many institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Current data have shown that PRAT size potentiates the lesions produced by other renal metabolic factors, such as abnormal insulin serum levels and increased glucose resistance or high triglycerides and uric acid levels, all these features being observed in patients with chronic kidney disease [ 10 , 46 ]. Furthermore, according to the results of a recent study, an increase of PRAT in patients with calcium phosphate apatite or uric acidic nephrolithiasis has been noticed [ 47 ]. Since it could not be specified whether there is a direct relationship between the occurrence of these lesions and PRAT volume, further research is needed to clarify this finding [ 47 ].…”
Section: Prat In Chronic Renal Pathologymentioning
confidence: 99%
“…Furthermore, according to the results of a recent study, an increase of PRAT in patients with calcium phosphate apatite or uric acidic nephrolithiasis has been noticed [ 47 ]. Since it could not be specified whether there is a direct relationship between the occurrence of these lesions and PRAT volume, further research is needed to clarify this finding [ 47 ].…”
Section: Prat In Chronic Renal Pathologymentioning
confidence: 99%
“…PRAT thickness could aggravate renal anomalies due to metabolic dysfunction such as abnormal insulin serum levels, high glucose or triglycerides and uric acid, all of which are reported in patients with CKD ( 129 ). Additionally, excess PRAT is detected in patients with calcium phosphate apatite or uric acid nephrolithiasis ( 177 ). However, future research into analyzing the detailed mechanism is warranted.…”
Section: Perirenal Adipose Tissue and Renal Diseasesmentioning
confidence: 99%